Effect of Suni-bug (Eurygaster spp.) Damage on Some Biochemical Properties of Bread Wheat Variety (Bezostaja) - DIRAMAN, HARUN (Asian Journal of Chemistry, 2010)
In this study, the effect of suni bug (Eurygaster spp) damage in different levels (0, 25 and 100 %) on some properties of wheat storage proteins (Bezostaja variety) such as total protein, wet gluten content, Perten gluten indexes, Pelshenke tests, soluble protein fractions (in water, 2 % trichloroacetic acid (TCA) and 70 % EtOH, insoluble protein fractions in 0.05 M acetic acid) have been investigated. It was seen that the sample decreased the Pelshenke test values and residue protein (insoluble in 0.05 M acetic acid) amount but the amounts of albumin, gliadin and non-nitrogen fractions (soluble in 2 % TCA) increased according to the levels of bug damage. The negative changes on the solubility properties of flour proteins with higher damage levels indicated the hydrolysis of peptide bonds by excessive proteolytic activity resulting from the injection of protease by the suni-bug during grain filling.